Toxic epidermal necrolysis and Stevens‐Johnson syndrome/toxic epidermal necrolysis overlap in pediatric patients with a focus on newer antiepileptic drugs: A 25‐year retrospective study at a single tertiary care center. Issue 4 (31st May 2021) - Gleghorn, Kristyna L.; Voigt, Charles; Kelly, Brent
Abstract: Background: Stevens‐Johnson syndrome (SJS) and toxic epidermal necrolysis Syndrome (TEN) are rare immune‐mediated diseases. Extensive research on adult triggers of SJS and TEN is available; however, research in children is more limited. Objective: We sought to investigate and report the experience with pediatric SJS and TEN in our center, identifying associated medications. Methods: A retrospective review from 1990 to 2015 at the Shriner's Burn Hospital in Galveston, Texas was performed to identify patients diagnosed with SJS, SJS/TEN overlap, and TEN. Data pertaining to demographic characteristics, medical history, physical exam, treatment, and outcomes were collected. Results: We identified SJS/TEN overlap or TEN in 51 patients. Antiepileptic drugs were the most common group of causative agents, closely followed by antibiotics. The most common causative agents were trimethoprim‐sulfamethoxazole, phenytoin, and lamotrigine used concomitantly with valproic acid. Newer generation agents, with the definition of agents approved after 1990, were the cause in 13/51 (25.5%) cases. Newer generation agents included lamotrigine, clobazam, and zonisamide. Seven patients died, resulting in a 13.7% mortality rate. Renal failure, liver failure, sepsis, and gastrointestinal involvement each had a statistically significant association with mortality. SCORTEN was statistically significantly greater in patients who died compared to children who lived (3 vs 2). Limitations: This is a retrospective study. Conclusion: Three drugs introduced into the market since 1990 have emerged as causes of SJS/TEN overlap and TEN: lamotrigine, clobazam, and zonisamide. These medications are being used more widely to treat seizures, as well as mood disorders. It is also important for clinicians to be aware of the extremely commonly used medications such as amoxicillin, tetracyclines, NSAIDs, and acetaminophen that can rarely cause SJS and TEN.